2017
DOI: 10.1080/09674845.2017.1297217
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a novel score for prediction of large oesophageal varices in patients with hepatitis c virus-induced liver cirrhosis

Abstract: PAP scores a non-invasive, inexpensive and simple score that could predict the presence of large oesophageal varices reducing the need of endoscopy. The PAP score has a superior AUC score than other scores, suggesting improved clinical value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Another study found that INR was correlated independently and significantly with liver fibrosis in chronic hepatitis C patients [16]. Recently, a study by Farid K et al [17] demonstrated that prothrombin-INR scores contributed to predicting the occurrence of large esophageal varices in patients with hepatitis C virus-induced liver cirrhosis. Therefore, the INR could be considered a potential indicator of liver fibrosis.…”
Section: Introductionmentioning
confidence: 98%
“…Another study found that INR was correlated independently and significantly with liver fibrosis in chronic hepatitis C patients [16]. Recently, a study by Farid K et al [17] demonstrated that prothrombin-INR scores contributed to predicting the occurrence of large esophageal varices in patients with hepatitis C virus-induced liver cirrhosis. Therefore, the INR could be considered a potential indicator of liver fibrosis.…”
Section: Introductionmentioning
confidence: 98%
“…demonstrated that no association was found between esophageal varices and AST/ALT ratio and AST/ALT at a cut‐off 1.71, with 59% sensitivity, 54% specificity, and an AUC of 0.53. This could be attributable to the effect of several variables on serum ALT, such as gender and body mass index, as well as hepatotoxic medications, which subsequently affect AST/ALT results 26 …”
Section: Discussionmentioning
confidence: 99%
“…However, this was in disagreement with Sebastiani et al ., 23 who showed that for the Lok score at a cut‐off >1.5, used to predict PHG, sensitivity was 71.3%, specificity was 68.3%, PPV was 50%, NPV was 84.2%, and AUC was 0.42. In addition, Farid K and his colleague mentioned that the combination of Lok index and Forns' index had an AUC of 0.80 with 90% NPV to exclude large OV or small OV 26 …”
Section: Discussionmentioning
confidence: 99%
“…To sum up, platelet parameters and related scoring systems such as PAP scores, AAR, APRI, GUCI, BRC score, Fibro-Alfa, FIB4, Lok, and Fibro-Q, have a certain value in predicting the degree of esophageal varices and collateral veins in patients with liver cirrhosis. 26,31,32 In many scoring systems, the predictive value of Lok index is better than other scoring systems, but because of its low AUROC value, it cannot replace the gold standard endoscopy, so we need to further expand the sample size to verify it. At same time, we will validate the conclusion with more sample number in further research due to the low number of sample in this study.…”
Section: Ta B L E 7 Multivariate Ordered Logistic Regression Analysismentioning
confidence: 99%